"Sky islands" in the eastern U.S.A.? — Strong phylogenetic structure in the Heuchera parviflora group (Saxifragaceae). Issue 2 (28th December 2018) - Folk, Ryan A.; Freudenstein, John V.
Abstract: Lineage delimitation using multiple sources of data has received renewed emphasis owing to the new possibilities offered by multi–locus datasets and model–based analyses. Species complexes displaying interrupted sky island–like distributions may be especially under–assessed by current taxonomies, warranting reexamination with new data and methodologies. We present a molecular and morphological study of the discontinuously distributed Heuchera parviflora complex (Saxifragaceae), with the aim of identifying genetic lineages that correlate with geography and morphology and may be worthy of taxonomic recognition in this contentious group. Concatenated analyses of the molecular data suggest four genetic lineages that are allopatric or (in one case) parapatric and correlate with major physiographic provinces. These lineages also correlate with morphological differentiation in the group and suggest taxonomically useful morphological characters. Independent, confirmatory coalescent approaches strongly support the four lineages identified by concatenation. However, morphological differentiation, though involving multiple characters, is relatively weak between two of the identified lineages. For this reason, in contrast with most coalescent studies we advocate the use of both specific and varietal rank, recognizing in total three species, one with two varieties.